2017
DOI: 10.1002/pds.4248
|View full text |Cite
|
Sign up to set email alerts
|

Changes in drug use patterns reported on the web after the introduction of ADF OxyContin: findings from the Researched Abuse, Diversion, and Addiction‐Related Surveillance (RADARS) System Web Monitoring Program

Abstract: Web Monitoring data are useful for capturing cross sections of Internet conversation reflecting reactions to new drug formulations. These data support the notion that users will gravitate to non-ADFs generally, and to immediate-release non-ADF opioid formulations, specifically, as long as these options remain on the market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
8
0
4
Order By: Relevance
“…Given the danger surrounding some drugs, these unsolicited expressions could shed light in areas that traditional survey instruments cannot. Examples of recent uses of social media data in research include discovering adverse drug events [ 12 ], studying addiction [ 13 ], tracking the popularity of marijuana concentrates [ 14 ], quantifying drug abuse [ 15 ], and characterizing discussion surrounding the introduction of an abuse-deterrent product [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the danger surrounding some drugs, these unsolicited expressions could shed light in areas that traditional survey instruments cannot. Examples of recent uses of social media data in research include discovering adverse drug events [ 12 ], studying addiction [ 13 ], tracking the popularity of marijuana concentrates [ 14 ], quantifying drug abuse [ 15 ], and characterizing discussion surrounding the introduction of an abuse-deterrent product [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Web Monitoring Program, established in 2014, focuses on the collection and organization of real-time web content about prescription drugs from over 150 million sites on the internet, including social media, blogs, and forums. The RADARS System Web Monitoring Program combines qualitative and quantitative data collection methods; a team of trained researchers collect daily opioid-related posts and manually code them for variables of interest [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a recent study in which the Internet was monitored for abuse-related discussions indicated that abusers are more likely to switch to non-ADF opioids than attempt to prepare reformulated ER oxycodone for non-oral abuse (21). There was no evidence of dose dumping from morphine ARER during any tested conditions, unlike the dose dumping noted with crushed ER morphine, which does not contain any abuse-deterrent properties.…”
Section: Discussionmentioning
confidence: 85%
“…2 To address challenges of quickly identifying newly emerging synthetic opioids, novel data sources such as web or social media data may serve as potential early warning systems. Prior work has mainly focused on automated identification of messages indicating misuse, 3 detection of online illicit pharmacies, evaluating opinions around certain compounds, 4 understanding spread of norms, and comparing online findings to survey data. 5 However, there is particularly limited work examining fentanyl and fentanyl analogs (now the leading cause of overdose deaths) and limited work that directly compares findings from these novel approaches to death data to describe how much lead time an early warning system based on online data could potentially provide.…”
Section: Introductionmentioning
confidence: 99%